Tail-anchored protein insertion by a single Get1/2 heterodimer - Zalisko, Benjamin E. (Cell Rep, 2017)
The Get1/2 transmembrane complex drives the insertion of tail-anchored proteins from the cytosolic chaperone Get3 into the endoplasmic reticulum membrane. Mechanistic insight into how Get1/2 coordinates this process is confounded by a lack of understanding of the basic architecture of the complex. Here we define the oligomeric state of full-length Get1/2 in reconstituted lipid bilayers by combining single-molecule and bulk fluorescence measurements with quantitative in vitro insertion analysis. We show that a single Get1/2 heterodimer is sufficient for insertion and demonstrate that the conserved cytosolic regions of Get1 and Get2 bind asymmetrically to opposing subunits of the Get3 homodimer. Taken together, our results define a simplified model for how Get1/2 and Get3 coordinate TA protein insertion.